The Mediating Role of Coping Style in the Relationship Between Sleep Quality and Burnout: A Cross-Sectional Study Among Psychiatric Nurses - Yin, Ming; Li, Weiqin; Yang, Qun; Yue, Yan; Fang, Xiaojia; Yang, Zhong; Wang, Xinda; Liu, Qin; Kong, Fanzhen; Ji, Caifang; Lv, Xiaoli; Wang, Hao; et al. (Frontiers in Psychiatry, 2022)
Background Although sleep quality is clearly associated with job burnout as shown in the existing research, the mechanism underpinning such relationship remains undefined. This work, thus, aimed to assess the current situation of sleep quality and burnout in Chinese psychiatric nurses, and to analyze the relationships between sleep quality, burnout and coping style, in order to provide possible targets to enhance mental health and wellbeing among psychiatric nurses. Method This cross-sectional study was carried out in seven rehabilitation centers located in four different regions of China. The Pittsburgh Sleep Quality Index, the Epworth Sleeping Scale, the Maslach Burnout Inventory General Survey, and the Coping Style Questionnaire were distributed to 853 nurses in various mental hospitals, with a total of 664 participants being recruited in the final research. Results The results of this current study showed a high prevalence of sleep disorders and burnout in Chinese psychiatric nurses. Moreover, emotional exhaustion (r = 0.456), cynicism (r = 0.323) and negative coping style (r = 0.191) in nurses were all positively correlated with total Pittsburgh Sleep Quality Index (PSQI) score, while professional efficacy (r = −0.079) and positive coping style (r = −0.140) were negatively correlated with total PSQI score. More interestingly, of all negative coping strategies, we found that self-blame had the most significant effect (β = 0.156). Conclusions The above results showed that coping style mediates the association of poor sleep quality with job burnout in Chinese psychiatric nurses. This study claimed that there is an urgent need to development the coping skills to sustain a healthy work life for nurses.